Estimating land use/land cover change impacts on vegetation response to drought under 'Grain for Green' in the Loess Plateau. (6th October 2021) - Ding, Yibo; Wang, Fengzuo; Mu, Qing; Sun, Yanan; Cai, Huanjie; Zhou, Zhaoqiang; Xu, Jiatun; Shi, Haiyun
Abstract: A series of serious environmental problems have appeared in North China, especially in the Loess Plateau. The 'Grain for Green Program' project has been implemented to address issues caused by vegetation degradation. Human beings play a key moderating role between drought and vegetation; however, it is not clearly understood how typical land cover changes from human activities impact the ability of vegetation to resist drought. To represent meteorological drought and vegetation dynamics, this study applied the standardized precipitation and evapotranspiration index and solar‐induced chlorophyll fluorescence. We investigated the vegetation response relationship to drought and how changing land cover affected it. The land cover changes associated with strategic human activity were also analyzed using the response relationship and environmental characteristics. Our results showed that land cover changes contributed to abnormal changes in vegetation dynamics and type. From 2001 to 2016, meteorological drought showed an insignificant difference in Loess Plateau. To a certain extent, land cover changes could extend vegetation response time with the implementation of the 'Grain for Green Progam'. Response time to the drought of different vegetation types in both changed and unchanged land cover showed an increasing trend from early‐period to later‐period. Similar response time to drought was among cropland, forest, grassland, construction land, and desert of unchanged land cover vegetation in different Grain for Green periods. Forest cover effectively improved vegetation response time and reduced vulnerability. This study improves the understanding of vegetation change and offers guidance for environmental protection projects and evaluating ecological restoration.